(untitled) (Fiep Bulletin - online, 2014)
Quality of life is an important element in the analysis of physical and emotional life, and the multidimensional character of this construct should be investigated. This study evaluated women’s perception of positive and negative feelings, self-esteem, body image and appearance during aging. This cross-sectional descriptive study enrolled 664 women 18 to 80 years from Vale do Sinos, Rio Grande do Sul (RS), Brazil, who were selected using convenience sampling. The WHOQOL-100 questionnaire was used to evaluate quality of life. This instrument is made up of different facets grouped in six domains: physical, psychological, level of independence, social relations, environment and spirituality. We used the psychological domain facets: positive and negative feelings, self-esteem, body image and appearance. The chi-square test and the SPSS 15.0 software were used for statistical analysis, and women were divided in three groups: 18 to 39 years (adult, n=301); 40 to 59 years (middle age, n=267); and older than 60 years (old, n=96). Data showed that middle-aged women enjoyed life less (p=0.00) and experienced fewer positive feelings (p=0.00) than adult and old women. Old women had fewer negative feelings, such as bad mood, despair, anxiety and depression (p=0.03); they also were the most optimistic about the future (p-0.00), the least concerned with problems associated with physical appearance (p=0.00), had the greatest confidence (p=0.01), and were the most satisfied with themselves (p=0.00). Although women have different psychological problems in different life phases, this study found that old women had more favorable and optimistic perceptions and knew how to deal with their positive and negative feelings better than women in the other age groups.